2020
DOI: 10.3389/fspor.2020.00068
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Resistance Exercise Training vs. High Intensity (Endurance) Interval Training to Fight Cardiometabolic Risk Factors in Overweight Men 30–50 Years Old

Abstract: Cardiovascular and cardiometabolic diseases are leading causes of death worldwide. Exercise favorably affects this problem, however only few invest (enough) time to favorably influence cardiometabolic risk-factors and cardiac morphology/performance. Time-effective, high-intensity, low-volume exercise protocols might increase people's commitment to exercise. To date, most research has focused on high-intensity interval training (HIIT), the endurance type of HIT, while corresponding HIT-resistance training proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A small number of studies have demonstrated the benefit of strength training programmes [ 6 , 10 ] but there are sufficient reviews and meta-analyses that indicate reductions in LDL-C and total cholesterol as well as increase of HDL [ 11 , 12 ] in addition to reduction of the HOMA-IR index. Strength training programmes promote more discreet reductions in cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have demonstrated the benefit of strength training programmes [ 6 , 10 ] but there are sufficient reviews and meta-analyses that indicate reductions in LDL-C and total cholesterol as well as increase of HDL [ 11 , 12 ] in addition to reduction of the HOMA-IR index. Strength training programmes promote more discreet reductions in cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%